2023
DOI: 10.3389/fphys.2023.1177829
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of bone disease in chronic kidney disease: from basics to renal osteodystrophy and osteoporosis

Armando Aguilar,
Laia Gifre,
Pablo Ureña-Torres
et al.

Abstract: Chronic kidney disease (CKD) is a highly prevalent disease that has become a public health problem. Progression of CKD is associated with serious complications, including the systemic CKD-mineral and bone disorder (CKD-MBD). Laboratory, bone and vascular abnormalities define this condition, and all have been independently related to cardiovascular disease and high mortality rates. The “old” cross-talk between kidney and bone (classically known as “renal osteodystrophies”) has been recently expanded to the card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 199 publications
0
3
0
Order By: Relevance
“…Previous research has demonstrated that osteoporosis prevalence is much higher in sufferers of CKD than in age-matched controls, with a loss in BMD launching at an early stage and CKD as a separate risk factor for osteoporosis (42)(43)(44). The complex and varied mechanisms that underlie this phenomenon are typically attributed to abnormalities in the metabolism of calcium and phosphorus, secondary hyperparathyroidism, abnormalities in bone conversion, deficiencies in 1,a-hydroxylase and vitamin D, metabolic acidosis, uremic toxins, microinflammatory states, among others (45)(46)(47). It might seem contrary to what we discovered.…”
Section: B Acontrasting
confidence: 86%
“…Previous research has demonstrated that osteoporosis prevalence is much higher in sufferers of CKD than in age-matched controls, with a loss in BMD launching at an early stage and CKD as a separate risk factor for osteoporosis (42)(43)(44). The complex and varied mechanisms that underlie this phenomenon are typically attributed to abnormalities in the metabolism of calcium and phosphorus, secondary hyperparathyroidism, abnormalities in bone conversion, deficiencies in 1,a-hydroxylase and vitamin D, metabolic acidosis, uremic toxins, microinflammatory states, among others (45)(46)(47). It might seem contrary to what we discovered.…”
Section: B Acontrasting
confidence: 86%
“…Bone abnormalities affect almost all patients with CKD requiring dialysis and the majority of patients with CKD stages 3–5 ( 27 , 38 ). So, we hypothesized an increased marrow fat in patients with late stages of chronic renal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Sustained high PTH levels in CKD cause a high turnover state in bone, where bone resorption and, in a lesser degree, bone formation are stimulated. The disturbed osteoblast activity results in disorganized bone formation, with an excessive amount of non-mineralized component of bone, leading to skeletal fragility and subsequent increased fracture risk, particularly at the peripheral skeleton ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease-mineral and bone disorder (CKD-MBD) is the term used to define the changes (laboratory abnormalities, bone abnormalities, and extra-skeletal calcifications) secondary to CKD. Secondary hyperparathyroidism (SHPT) results from CKD-MBD dysregulation and consists of hyperphosphatemia, [66].…”
Section: Management Of Mineral and Bone Metabolism Disordersmentioning
confidence: 99%